The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2014
DOI: 10.1055/s-0034-1368691
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of 88 Patients with Diffuse and “Benign” Perimesencephalic Subarachnoid Hemorrhage

Abstract: Our data demonstrate that although the patients with perimesencephalic SAH fared better than those with diffuse SAH, their outcomes were worse than those of similar patients with PMSAH who have been previously reported in the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…[ 18 , 19 ] However, patients with PNSAH were associated with an excellent prognosis with an uncomplicated illness course and a low risk of rebleeding, cerebral vasospasm, hydrocephalus, delayed cerebral ischemia, no decrease in quality of life and death. [ 4 , 5 , 7 , 18 20 ] But it has been reported that cognitive impairment was common in this cohort. [ 6 ] Several risk factors for PNSAH have been suggested such as younger age, female sex, and smoking.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…[ 18 , 19 ] However, patients with PNSAH were associated with an excellent prognosis with an uncomplicated illness course and a low risk of rebleeding, cerebral vasospasm, hydrocephalus, delayed cerebral ischemia, no decrease in quality of life and death. [ 4 , 5 , 7 , 18 20 ] But it has been reported that cognitive impairment was common in this cohort. [ 6 ] Several risk factors for PNSAH have been suggested such as younger age, female sex, and smoking.…”
Section: Discussionmentioning
confidence: 87%
“…[ 3 ] In contradistinction to aneurysmal SAH, PNSAH has an excellent prognosis with an uneventful clinical course and a low risk of vasospasm, rebleeding, hydrocephalus, and delayed cerebral ischemia. [ 4 , 5 ] However, many patients with PNSAH complained of functional decline which prevented them from returning to work. [ 6 ] The pathogenesis and mechanisms of the PNSAH are controversial.…”
Section: Introductionmentioning
confidence: 99%